A sociological autopsy lens on older adult suicide in rural Australia: Addressing health, psychosocial factors and care practices at the intersection of policies and institutions. (September 2021) - Fitzpatrick, Scott J.; Read, Donna; Brew, Bronwyn K.; Perkins, David
Abstract: This paper examines the interrelationship between suicide, health, socioeconomic, and psychosocial factors in contributing to suicide in older adults in rural Australia. Drawing on a coronial dataset of suicide cases and a mixed methods sociological autopsy approach, our study integrated a quantitative analysis of 792 suicide cases with a qualitative analysis of medico-legal reports from 30 cases. The sociological autopsy provided novel insights into the entanglement of policy and service provision at the state-level with individual end-of-life decisions. Particular attention is drawn to age and gendered dimensions of suicide, especially in relation to health and social issues. The study showed a continuity between suicide and the patterning of an individual's life course, including experiences and consequences of inequality and marginality; a desire to meet culturally–normative ideals of autonomy; and a fragmented, under-funded, and intimidating social care system that offered limited options. Highlights: Sociological autopsy applied to unique coronial dataset of older adult suicide. Combines quantitative and qualitative analyses of data from medico-legal reports. Age and gendered differences in health and social issues related to suicide. State-level policies and practices intersect with individual end-of-life decisions. Imperative of prevention creates harmful environments and consequences.